FIGURE OF SPEECH: SHIFT IN STYLE IN THE POETRY OF W.D HOWELLS AND T.S ELLIOT - Saputra, Danang Rendi; Azzahra, Ifatunnisa; Alfarisi, Salman (Journal of Language and Literature, 2023)
This research aims to analyze the stylistic turn in the poems about Realism entitled "Dead" and "If" by William Dean Howell and “The Fire Sermon”and "The Burial of Dead" by T.S. Eliot about Modernism. This study uses Zienkowski's (2011) theory to show the language style embodied in literary works. This research uses a qualitative descriptive design to reveal and investigate the phenomenon of style embodied in the poet. The data taken are words, phrases, and sentences related to the discourse of beauty. Data to support this research is taken from articles, journals, websites, and previous studies with the same topic but with different objects. Based on theory and analysis, the researcher argues that the poem "If," an early poem by William, uses a lot of personification and metaphor to express strong feelings and ideas, often using the language of nature. Meanwhile, in the poem "Dead," William also displays a very contrasting style. The use of personification and metaphor. "Burial of the Dead" from "The Waste Land" uses a fragmented structure and a large number of metaphors and metonymies to depict the fragmentation and loss of meaning in society. In "The Fire Sermon," Eliot explores the spiritual and sexual disillusionment of the post-World War I era. He incorporates various metonymic sounds, allusions and imagery. Thus, this identification can reveal the correlation between the poetry of William Dean Howells and T.S Elliot.